Profil Moderasi Beragama Mahasiswa Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Maulana Malik Ibrahim Malang - Priatmoko, Sigit; Sugiri, Wiku Aji; Amelia, Rizki (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
This study aims to explore the profile of religious moderation of prospective students of Madrasah Ibtidaiyah teachers. This goal is motivated by the strategic position of Madrasah Ibtidaiyah (MI) teachers in efforts to mainstream religious moderation and prevent radicalism from an early age. The researcher used a quantitative approach with a descriptive quantitative type. Respondents in this study were 106 students, with details of 81 (76.4%) Semester I students, 14 (13.2%) Semester V students, 9 (8.5%) Semester VII students, the remaining 2 (1.9%) ) Semester III students and 1 (0.9%) Semester VI students. Collecting data using a closed questionnaire instrument with a total of 25 questions. The questionnaire was created using the Google Form application and distributed through the student batch Whatsapp group. The questions in the questionnaire are based on four indicators of religious moderation developed by the Ministry of Religion of the Republic of Indonesia, namely (1) national commitment, (2) tolerance, (3) anti-violence, and (4) acceptance of tradition. Data analysis used descriptive statistical analysis techniques where the researcher described the data collected as they were without generalizing. The results showed that almost all respondents met the indicators of religious moderation required by the Ministry of Religion of the Republic of Indonesia. This is evidenced by the high percentage of agree and strongly agree with the four indicators. However, even so, there are still respondents who show resistance to these four indicators. This fact has become a record of the Maulana Malik Ibrahim State Islamic University of Malang, especially the Madrasah Ibtidaiyah Teacher Education study program (PGMI).